The cytotoxic activity of extracts from the biomass and fruit bodies of Isaria tenuipes VHI-2 fungus on MCF-7 cancer cell line - Pham, T. M. N.; Ha, T. N.; Nguyen, V. K. D.; Nguyen, T. H.; Nguyen, C. D.; Dinh, M. H.; Ngo, K. S. (International Journal of Agricultural Technology, 2020)
Isaria tenuipes is an insect-parasitic fungus, an anamorph of Cordycep takamontana and used a nutraceutical in traditional Chinese medicine for cancer patients. In vitro cytotoxic activity of extracts from I. tenuipes VHI-2 on cancer cell. This I. tenuipes strain was collected in the Langbiang mountain, Tam Dao and Ba Vi national parks from Vietnam and cultured to collect biomass and fruit bodies on liquid at optimal conditionat 20-220C. We obtained 7 extracts from biomass and 6 extracts from fruit bodied via percolation method with ethanol (EtOH) and liquid-liquid extraction method by four different solvents: petroleum ether (60 – 80oC) (PE), etyl acetate (EA), butanol (BuOH) and water (W), successively. The extracts were proved in vitro cytotoxic activity against MCF-7 breast carcinoma cell line by the sulforhodamine B (SRB) assay at 100 µg/mL concentration for 48 hours. The result showed that fruit-body extracts were shown higher cytotoxic potential than biomass extracts but all were below 50%. Specifically, EA extract of fruit body had the highest with inhibited percentage 44.83 ± 6.88%, the other expressed approximate activities as in PE, BuOH, W, PS with percentage of inhibition were 9.86 ± 5.44%, 26.98 ± 2.82%, 7.97 ± 6.88% and 3.40 ± 3.06% respectively. Meanwhile, only PS extract of biomass has active (31.35 ± 6.08%). These results indicated that I. tenuipes VHI-2 express low ability to inhibit MCF-7 cancer cell line and more researches are needed on other cancer cell lines to determine correctly potential of I. tenuipes VHI-2 in cancer treatment.